2009
DOI: 10.1038/pcan.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic role of syndecan-2 in prostate cancer

Abstract: Syndecans are a four-member family of transmembrane heparan sulphate proteoglycans that have different functions in cell signalling, adhesion, cytoskeleton organization, migration, proliferation, and angiogenesis. Several studies investigated the role of syndecan-2 (SDC2) in different carcinomas; however, only one being focused on SDC2 in prostate cancer. SDC2 expression and relationship with established prognostic features were assessed in a cohort of 86 patients treated with radical prostatectomy for clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
1
23
2
1
Order By: Relevance
“…23 The evidence presented in this work supports the idea that the syndecan-1 serum level may represent a novel clinical marker for prostate cancer. 13,14,18 Unexpectedly, we were not able to find a coordinated downregulation of syndecan-1 membrane expression followed by an upregulation of syndecan-2 membrane expression as part of the epithelial-mesenchymal transition. Nonetheless, we observed increased syndecan-2 cytoplasmic expression in prostate cancer cells, which correlates with a high risk of biochemical recurrence.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…23 The evidence presented in this work supports the idea that the syndecan-1 serum level may represent a novel clinical marker for prostate cancer. 13,14,18 Unexpectedly, we were not able to find a coordinated downregulation of syndecan-1 membrane expression followed by an upregulation of syndecan-2 membrane expression as part of the epithelial-mesenchymal transition. Nonetheless, we observed increased syndecan-2 cytoplasmic expression in prostate cancer cells, which correlates with a high risk of biochemical recurrence.…”
Section: Discussioncontrasting
confidence: 64%
“…We confirmed that syndecan-1 and, interestingly, syndecan-2, were both expressed in epithelial cells of normal and pathological prostate tissue. Popovic et al 14 have also reported syndecan-2 expression in prostate cancer and prostatic intraepithelial neoplasia samples but not in normal prostate tissue. In our work, we found expression of syndecan-2 at the membranes of basal cells in non-malignant tissue (BPH samples).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…SDC2 is a cell surface receptor and appears to play diverse and possibly conflicting roles in cancer: SDC2 downregulation was associated with poor prognosis in esophageal squamous cell carcinoma, 36 whereas SDC2 overexpression was associated with poor prognosis in prostate cancer tissue. 37 KCNK12 encodes a member of the potassium channel superfamily, and was shown to be hypermethylated in 32 out of 77 colorectal tumors. 7 Analysis of the DMRs in a large independent cohort of CRC and preferably using an orthogonal analysis method should be performed to evaluate their frequency of hypermethylation in CRC, as well as their clinical value.…”
Section: 28mentioning
confidence: 99%
“…Moreover, colon cancer cells cultured on syndecan-2 ectodomain or syndecan-2 antibody show increased adhesion and spreading (28). Syndecan-2 is also overexpressed in about 90% of prostate cancer patients, and the increased syndecan-2 expression enhances the growth of prostate tumor cells (29). In contrast to other syndecans, which generally function as tumor promoters, syndecan-4 apparently functions as a tumor suppressor.…”
Section: Syndecans and Cancermentioning
confidence: 99%